Selected dechlorination of triclosan by high-performance g-C3N4/Bi2MoO6 composites: Mechanisms and pathways. (January 2023) - Yu, Bingzhi; Yan, Wen; Meng, Yunjuan; Zhang, Yinan; Li, Xizi; Li, Yan; Zhong, Yuchi; Ding, Jiafeng; Zhang, Hangjun
Abstract: Environmental-friendly and efficient strategies for triclosan (TCS) removal have received more attention. Influenced by COVID-19, a large amount of TCS contaminants were accumulated in medical and domestic wastewater discharges. In this study, a unique g-C3 N4 /Bi2 MoO6 heterostructure was fabricated and optimized by a novel and simple method for superb photocatalytic dechlorination of TCS into 2-phenoxyphenol (2-PP) under visible light irradiation. The as-prepared samples were characterized and analyzed by XRD, BET, SEM, XPS, etc. The rationally designed g-C3 N4 /Bi2 MoO6 (4:6) catalyst exhibited notably photocatalytic activity in that more than 95.5% of TCS was transformed at 180 min, which was 3.6 times higher than that of pure g-C3 N4 powder. This catalyst promotes efficient photocatalytic electron-hole separation for efficient dechlorination by photocatalytic reduction. The samples exhibited high recyclable ability and the dechlorination pathway was clear. The results of Density Functional Theory calculations displayed the TCS dechlorination selectivity has different mechanisms and hydrogen substitution may be more favorable than hydrogen abstraction in the TCS dechlorination hydrogen transfer process. This work will provide an experimental and theoretical basis for designing high-performance photocatalysts to construct the systems of efficient and safe visible photocatalytic reduction of aromatic chlorinated pollutants, such as TCS in dechlorinated waters. Graphical abstract: Image 1 Highlights: A direct heterojunction photocatalyst was synthesized. The g-C3 N4 /Bi2 MoO6 composites enhanced the dechlorination performance. Bi2 MoO6 combining improves charge separation of g-C3 N4 . DFT is a powerful method for the study of TCS dechlorination.